Diseño y construcción de un sistema portátil de pruebas de estanqueidad para locaciones cerradas, en base a las exigencias de la norma NFPA 2001 - Cahuasquí Molina, Jonathan Moises (2017)
ENERGYPETROL is an Ecuadorian company that has 15 years of experience in the design and construction of fire and gas detection systems, in which one of the ways to suppress fire is through the application of clean extinguishing agents such as FM- 200, for which it is necessary to carry out a leakproofness test at the location. The ENERGYPETROL company sponsors the development of an automatic, modular and portable system which allows the leakage tests to be carried out in order to verify, certify and locate leaks in the enclosure, in order to verify if it is sufficiently closed to keep Extinguishing agent for a certain time and in the percentage of concentration of design that guarantees the fire extinction, all this process is established by the norm NFPA 2001 that tries to determine the leakages using a door fan, which allows to emulate the conditions of a Discharge of the fire system, obtaining and recording flow and pressure variables in order to predict the establishment time that the extinguishing agent will remain in the location. The results of these tests through a technical report validate to the client that the location is adequate to apply the extinguishing agent, guaranteeing the protection of the fire system in a real fire alarm, in addition to collaborating with the conservation of the environment.